Predictors of falls and hospital admissions in people with cognitive impairment in day-care: role of multimorbidity, polypharmacy, and potentially inappropriate medication - Scheel, Jennifer; Luttenberger, Katharina; Grässel, Elmar; Kratzer, André; Donath, Carolin (BMC Geriatrics, 2022)
Background Multimorbidity, polypharmacy, and potentially inappropriate medication (PIM) pose challenges for the care of people with cognitive impairment. The aim of the present study is to explore whether multimorbidity, polypharmacy, and PIM predict falls and hospital admissions in a sample of people with cognitive impairment in day-care centers in Germany. Methods We used data from the German day-care study (multicenter longitudinal study, n = 433). Multimorbidity was defined as >= 2 chronic diseases. Polypharmacy was defined as prescriptions to >= 5 drugs. Potentially inappropriate medication was defined as scoring on the PRISCUS list. Binary logistic regression analyses were computed to determine whether multimorbidity, polypharmacy, and potentially inappropriate medication at t0 predicted falls and hospital admissions as outcomes at t1 (six months later). Results The rate of multimorbidity and polypharmacy was 87.8% and 60.3%, respectively. 15.9% of the people with cognitive impairment received PIM / PRISCUS-listed drugs, 43.6% ACB-listed drugs, and 52.7% CNS depressant drugs. Falls and hospital admissions during follow-up were prevalent in 19.4% and 24.7% of the people with cognitive impairment. Both were significantly predicted by the total number of drugs (falls: OR = 1.152, p = 0.001, overall model: p < 0.001; hospital admissions: OR = 1.103, p = 0.020, overall model: p = 0.001), even if regression analyses were controlled for the number of comorbidities. Conclusions Polypharmacy and potentially inappropriate medication are highly prevalent in people with cognitive impairment in German day-care centers. The number of drugs and appropriateness of medication seem to be crucial for the risk of falls and hospital admissions. Polypharmacy and PIM should be critically reviewed by healthcare providers and avoided as much as and whenever possible.
CRIS-Team WoS Importer:2022-08-26